2022
DOI: 10.1002/biof.1842
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid may inhibit immune evasion of colorectal cancer cells through targeting immune checkpoint and immunomodulator genes and their controlling microRNAs

Abstract: Colorectal cancer is one of the major concerns in both developed and developing societies. Because of the serious side effects of the current treatments, novel therapy agents have been developed that target immune checkpoint and immunomodulatory molecules in the tumor environment. Therefore, this study investigates the effect of docosahexaenoic acid (DHA) fatty acid on the expression of immune checkpoint molecule, PD‐L1, and immunomodulatory molecules, CD47 and CD39, and their controlling miRNAs in the colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…28 In addition, DHA caused an increase of PTEN in mRNA and protein level of expression so the phosphorylation of the p65 subunit of NF-kB was restrained and VEGF expression was reduced in MDA MB-231 cells. 28 Anti-immunosuppressive effect of DHA has been reported by Fadaee et al 29 In his analysis, DHA suppressed the level expression of immune checkpoint molecules in both normoxic and hypoxic conditions in colorectal cancer cells. 29 Furthermore, lipid deregulation, cell cycle impairment, and oxidative stress were other effects of DHA.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…28 In addition, DHA caused an increase of PTEN in mRNA and protein level of expression so the phosphorylation of the p65 subunit of NF-kB was restrained and VEGF expression was reduced in MDA MB-231 cells. 28 Anti-immunosuppressive effect of DHA has been reported by Fadaee et al 29 In his analysis, DHA suppressed the level expression of immune checkpoint molecules in both normoxic and hypoxic conditions in colorectal cancer cells. 29 Furthermore, lipid deregulation, cell cycle impairment, and oxidative stress were other effects of DHA.…”
Section: Discussionmentioning
confidence: 82%
“…28 Anti-immunosuppressive effect of DHA has been reported by Fadaee et al 29 In his analysis, DHA suppressed the level expression of immune checkpoint molecules in both normoxic and hypoxic conditions in colorectal cancer cells. 29 Furthermore, lipid deregulation, cell cycle impairment, and oxidative stress were other effects of DHA. 24 The inverse correlation between mTOR expression and miR-101 and miR-214 expression has been validated in several types of human carcinomas.…”
Section: Discussionmentioning
confidence: 82%
“…According to researches, a negative correlation has been discovered between the survival rate of sufferers from BC and the expression of PD-L1 [ 42 ]. Fadaee et al showed that DHA caused down-regulating the expression of PD-L1 in protein level in human colorectal cancer cell lines [ 43 ]. Also, Zhang et al reported that DHA decreased the expression of PD-L1 in lung cancer by rising degradation of ubiquitin-proteasome in vitro and in vivo [ 44 ].…”
Section: Discussionmentioning
confidence: 99%